Insights into HLA-G Genetics Provided by Worldwide Haplotype Diversity - Castelli, Erick C.; Ramalho, Jaqueline; Porto, Iane O. P.; Lima, Thálitta H. A.; Felício, Leandro P.; Sabbagh, Audrey; Donadi, Eduardo A.; Mendes-Junior, Celso T. (Frontiers in Immunology, 2014)
Human Leucocyte Antigen G (HLA-G) belongs to the family of nonclassical HLA class I genes, located within the major histocompatibility complex (MHC). HLA-G has been the target of most recent research regarding the function of class I nonclassical genes. The main features that distinguish HLA-G from classical class I genes are: a) limited protein variability; b) alternative splicing generating several membrane bound and soluble isoforms; c) short cytoplasmic tail; d) modulation of immune response (immune tolerance); e) restricted expression to certain tissues. In the present work, we describe the HLA-G gene structure and address the HLA-G variability and haplotype diversity among several populations around the world, considering each of its major segments (promoter, coding and 3’untranslated regions). For this purpose, we developed a pipeline to reevaluate the 1000Genomes data and recover miscalled or missing genotypes and haplotypes. It became clear that the overall structure of the HLA-G molecule has been maintained during the evolutionary process and that most of the variation sites found in the HLA-G coding region are either coding synonymous or intronic mutations. In addition, only a few frequent and divergent extended haplotypes are found when the promoter, coding and 3’ untranslated regions are evaluated together. The divergence is particularly evident for the regulatory regions. The population comparisons confirmed that most of the HLA-G variability has originated before human dispersion from Africa and that the allele and haplotype frequencies have probably been shaped by strong selective pressures.